Molecular characterization of the Schistosoma mansoni zinc finger protein SmZF1 as a transcription factor. - Marcela G Drummond; Carlos E Calzavara-Silva; Diego S D'Astolfo; Fernanda C Cardoso; Matheus A Rajão; Marina M Mourão; Elisandra Gava; Sérgio C Oliveira; Andréa M Macedo; Carlos R Machado; Sérgio D J Pena; Gregory T Kitten; et al. (Public Library of Science (PLoS), 2009)
BACKGROUND: During its development, the parasite Schistosoma mansoni is exposed to different environments and undergoes many morphological and physiological transformations as a result of profound changes in gene expression. Characterization of proteins involved in the regulation of these processes is of importance for the understanding of schistosome biology. Proteins containing zinc finger motifs usually participate in regulatory processes and are considered the major class of transcription factors in eukaryotes. It has already been shown, by EMSA (Eletrophoretic Mobility Shift Assay), that SmZF1, a S. mansoni zinc finger (ZF) protein, specifically binds both DNA and RNA oligonucleotides. This suggests that this protein might act as a transcription factor in the parasite. METHODOLOGY/PRINCIPAL FINDINGS: In this study we extended the characterization of SmZF1 by determining its subcellular localization and by verifying its ability to regulate gene transcription. We performed immunohistochemistry assays using adult male and female worms, cercariae and schistosomula to analyze the distribution pattern of SmZF1 and verified that the protein is mainly detected in the cells nuclei of all tested life cycle stages except for adult female worms. Also, SmZF1 was heterologously expressed in mammalian COS-7 cells to produce the recombinant protein YFP-SmZF1, which was mainly detected in the nucleus of the cells by confocal microscopy and Western blot assays. To evaluate the ability of this protein to regulate gene transcription, cells expressing YFP-SmZF1 were tested in a luciferase reporter system. In this system, the luciferase gene is downstream of a minimal promoter, upstream of which a DNA region containing four copies of the SmZF1 putative best binding site (D1-3DNA) was inserted. SmZF1 increased the reporter gene transcription by two fold (p</=0.003) only when its specific binding site was present. CONCLUSION: Taken together, these results strongly support the hypothesis that SmZF1 acts as a transcription factor in S. mansoni.